Development of a sexual dimorphism in a central pattern generator driving a rhythmic behavior: The role of glia‐mediated potassium buffering in the pacemaker nucleus of the weakly electric fish Apteronotus leptorhynchus. Issue 1 (5th March 2020) - Zupanc, Günther K. H.
Abstract: Central pattern generators play a critical role in the neural control of rhythmic behaviors. One of their characteristic features is the ability to modulate the oscillatory output. An important yet little‐studied type of modulation involves the generation of oscillations that are sexually dimorphic in frequency. In the weakly electric fish Apteronotus leptorhynchus, the pacemaker nucleus serves as a central pattern generator that drives the electric organ discharge of the fish in a one‐to‐one fashion. Males discharge at higher frequencies than females—a sexual dimorphism that develops under the influence of steroid hormones. The two principal neurons that constitute the oscillatory network of the pacemaker nucleus are the pacemaker and relay cells. Whereas the number and size of the pacemaker and relay cells are sexually monomorphic, pronounced sex‐dependent differences exist in the morphology, and subcellular properties of astrocytes, which form a syncytium closely associated with these neurons. In females, compared to males, the astrocytic syncytium covers a larger area surrounding the pacemaker and relay cells and exhibits higher levels of expression of connexin‐43 expression. The latter indicates a strong gap‐junction coupling of the individual cells within the syncytium. It is hypothesized that these sex‐specific differences result in an increased capacity for buffering of extracellular potassium ions, thereby lowering the potassium equilibrium potential, which, in turn, leads to a decrease in the oscillation frequency. This hypothesis has received strong support from simulations based on computational models of individual neurons and the whole neural network of the pacemaker nucleus.